STUDY OF EXTRA VIRGIN OLIVE OILS: EFFECTS OF THE FORMATION OF PYROPHEOPHYTIN A AND ITS RELATIONSHIP WITH THE QUALITY LOSSES OF THESE OILS - Mustapha Dibane, Abdelfattah El mahbouby, Miloudi Hlaibi (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Pyropheophytin A (PPP), generated at high levels through heat treatment, can significantly impact the quality of virgin oil. To address this, we devised a novel chromatographic method employing HPLC with UV-Visible detection to quantify PPP levels. We conducted an analysis on eighteen samples of extra virgin olive oils sourced from various regions in Morocco, assessing parameters such as free acidity, peroxide value, specific UV extinction, total phenols content, chlorophyll and carotenoid contents, tocopherols, and PPP percentage. Our results were revealing, indicating that certain samples surpassed the maximum acceptable PPP level of 17%, thereby posing a notable threat to oil quality.